2015
DOI: 10.1111/jns.12114
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and severity of vincristine‐induced peripheral neuropathy in children with acute lymphoblastic leukemia

Abstract: Vincristine, a critical component of combination chemotherapy treatment for pediatric acute lymphoblastic leukemia (ALL), can lead to vincristine-induced peripheral neuropathy (VIPN). Longitudinal VIPN assessments were obtained over 12 months from newly diagnosed children with ALL (N = 128) aged 1–18 years who received vincristine at one of four academic children’s hospitals. VIPN assessments were obtained using the Total Neuropathy Score-Pediatric Vincristine (TNS©-PV), National Cancer Institute Common Termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
111
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(122 citation statements)
references
References 33 publications
7
111
3
1
Order By: Relevance
“…Therefore, the degree to which the neonatal rat model fully recapitulates the clinical phenotype seen after pediatric VNC exposure remains unclear. For example, although motor dysfunction and loss of deep tendon reflexes are observed clinically in pediatric VNC-induced neuropathy [31,36,51,52,65], we did not observe alterations in either gross or fine motor skills in our experiments (Fig. 2).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Therefore, the degree to which the neonatal rat model fully recapitulates the clinical phenotype seen after pediatric VNC exposure remains unclear. For example, although motor dysfunction and loss of deep tendon reflexes are observed clinically in pediatric VNC-induced neuropathy [31,36,51,52,65], we did not observe alterations in either gross or fine motor skills in our experiments (Fig. 2).…”
Section: Discussioncontrasting
confidence: 51%
“…In humans, sensory testing has revealed VNC-induced impairments in temperature sensation. Adults with VNC-induced neuropathy are more sensitive to noxious cold stimuli and have elevated warm detection thresholds [16], while children are less likely to discern differences in temperature throughout the first year of VNC treatment when innocuous cold objects are applied to the skin [36,37]. Unfortunately, to our knowledge, sensitivities to noxious cold or heat stimuli have not been evaluated in the pediatric population following VNC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We do not know why this higher frequency of neuropathy since chemotherapy doses adjusted to the weight of the patient were used. In studies that have been conducted to measure chemotherapy-induced neuropathy in children with acute lymphoblastic leukemia, the most frequent cause has been vincristine treatment, which turned out to be dose dependent, and in which it has been observed that most of these complications have been found two weeks after administration of vincristine (17) Lavoie Smith et al, used the Neuropathy score pediatric vincristine scale in a total of 128 patients, receiving 1.5 mg/m 2 of vincristine, found a 78% of peripheral neuropathy (25) which is exactly similar to the finding observed in present study.…”
Section: Discussionmentioning
confidence: 99%
“…While the reported incidence rates vary considerably—depending on the severity of symptoms, diagnostic criteria and concomitant use of other neurotoxic agents—most patients receiving vincristine develop some degree of sensory peripheral neuropathy at a cumulative dose of >4 mg/m 2 (Ramchandren et al, 2009; Toopchizadeh et al, 2009; Seretny et al, 2014; Lavoie Smith et al, 2015; Tay et al, 2017). …”
Section: Cancer Chemotherapy: Drug Mechanism Of Action and Metabolitesmentioning
confidence: 99%